Recuros didacticos elaborados con material reciclable, para mejorar el aprendizaje de los niños y niñas del segundo grado de educacion general básica,en el área de entorno natural y social bloque 6 soy un ser vivo en la escuela de educación general básica Lauro Damerval Ayora Nº2 barrio La Tebaida parroquia San Sebastian canton y provincia de Loja. Periodo de Loja academico 2014-2015. - Sarango Valdez, Erika Joanna (2017)
In the present research topic called DIDACTIC RESOURCES ELABORATED WITH RECYCLABLE MATERIAL, TO IMPROVE THE LEARNING OF CHILDREN OF THE SECOND GRADE OF BASIC GENERAL EDUCATION, IN THE AREA OF NATURAL AND SOCIAL ENVIRONMENT, BLOCK 6. I AM A LIVING, IN THE SCHOOL OF BASIC GENERAL EDUCATION "LAURO DAMERVAL AYORA Nº 2", LA TEBAIDA NEIGHBORHOOD, SAN SEBASTIÁN PARK, CANTON AND STATE PROVINCE, ACADEMIC PERIOD 2014-2015. The research was pre-experimental, cross-sectional, descriptive and field. The methods used were analytical, synthetic, deductive, scientific, participatory, statistical and workshop diagnosis that allowed to systematize, represent and interpret empirical information. The techniques used were direct observation and interview through his instrument the questionnaire, applied to 15 students and a teacher of the second degree. The results of the research allowed us to determine that thanks to the use of didactic material made from recyclable material students can improve their learning and therefore be active, reflexive, constructors of their own learning